Cerebral palsy in Morocco: state of affairs and challenges - Najib Kissani; Reine Joephane Bikouta Ouadika; Hafid Arabi; Saloua Khalfaoui; Youness Abdelfettah (Amaltea Medical Publishing House, 2022)
Cerebral palsy (CP) constitutes a major public health problem in Morocco; there is a lack of prevalence and incidence studies. Objectives. The aim of our work is to study and analyze the epidemiological profile of disability, list the challenges and pitfalls concerning the management of CP in Morocco and developing countries, and highlight practical recommendations for health policymakers in terms of CP in particular and disability in general. Material and methods. Authors performed a literature search using MEDLINE, EMBASE, SCIENCE DIRECT, and Google scholar, but also searched in international and local journals to identify articles that examined CP in Morocco. Combination of keywords, such as "Cerebral Palsy" "disability" and "nervous system", and matching it with "Morocco", or other developing countries. Outcomes. There are an unsatisfactory number of specialists in physical medicine, lack of good collaboration between specialists involved in CP management and physiotherapists. This situation is more pronounced in small cities and rural areas. However, in Morocco compared to other developing countries, as in Sub-Saharan Africa, the situation is much better. Conclusion. CP is becoming a priority of Moroccan ministry of health and ministry of social affairs and huge improvements are made, mainly in university hospitals, the use of new techniques and reducing the management gap of regional hospitals, and rural areas with the recent use of telerehabilitation.